2021
DOI: 10.1039/d1nj03624f
|View full text |Cite
|
Sign up to set email alerts
|

Metal phosphide CuP2 as a promising thermoelectric material: an insight from a first-principles study

Abstract: In the search for better thermoelectric materials, metal phosphides have not been considered to be viable candidates so far, due to their large lattice thermal conductivity. Here we study thermoelectric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…CuP 2 has recently been proposed as a potential thermoelectric material. 12,13 Our measurements on a CuP 2−y film confirm that the lattice contribution to its thermal conductivity is indeed sufficiently low for thermoelectric applications. However, the thermoelectric figure of merit zT at room temperature is still low for all investigated compositions (Fig 7(d)) due to low power factors (Fig S8, Supporting Information).…”
Section: F Thermoelectric Characterizationsupporting
confidence: 57%
See 1 more Smart Citation
“…CuP 2 has recently been proposed as a potential thermoelectric material. 12,13 Our measurements on a CuP 2−y film confirm that the lattice contribution to its thermal conductivity is indeed sufficiently low for thermoelectric applications. However, the thermoelectric figure of merit zT at room temperature is still low for all investigated compositions (Fig 7(d)) due to low power factors (Fig S8, Supporting Information).…”
Section: F Thermoelectric Characterizationsupporting
confidence: 57%
“…Similar to other P-rich phosphides, bulk synthesis of CuP 2 as a single-crystal or powder is well established [5][6][7][8][9][10] but there are no reports of thin-film growth. CuP 2 is a semiconductor that has been proposed as a solar absorber, 11 thermoelectric material, 12,13 electrocatalyst for hydrogen-and oxygen evolution, 14 and as a component in composite anode materials for Li- [15][16][17] and Na-based batteries. 18,19 Although CuP 2 has been incorporated in electrochemical devices, its optoelectronic and thermoelectric characterization is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…56 The constant relaxation time approximation (CRTA) was applied, using the carrier lifetime τ set to be a single and isotopic value. In this work, we assessed the carrier lifetime τ for CsAg 5 Q 3 as a function of temperature within the deformation potential theory (DPT), 57,58 by considering the influence of acoustic phonon modes on electronic bands with the following equation, 57–59 where C , D and m * are the elastic constant, deformation potential and effective mass of carrier, respectively. We calculated the electronic band structures using a denser k -point mesh of 16 × 16 × 48, from which the effective mass m * was obtained within the single band approximation.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we assessed the relaxation time of charge carrier by use of the deformation potential theory (DPT), which is a key quantity for determining the electronic transport properties. Within this approach, the relaxation time s is calculated as a function of temperature by considering the electron-phonon interactions mainly contributed from the acoustic phonon modes with the following formula, 37,46…”
Section: Methodsmentioning
confidence: 99%
“…In the meantime, first-principles calculations revealed that the ZT value of CuP 2 can reach over 1.3 at 700 K by optimizing the hole concentration, highlighting a certain possibility of applying metal phosphides to thermoelectric devices. 37 …”
Section: Introductionmentioning
confidence: 99%